Efficacy of Smart Speaker-Based Metamemory Training in Older Adults: Case-Control Cohort Study - Kim, Jeongsim; Shin, EunJi; Han, KyungHwa; Park, Soowon; Youn, Jung Hae; Jin, Guixiang; Lee, Jun-Young (JMIR Publications, 2021)
BackgroundMetamemory training (MMT) is a useful training strategy for improving cognitive functioning in the older adult population. Despite the advantages, there are limitations imposed by location and time constraints. ObjectiveThis study aimed to develop a smart speaker-based MMT program and evaluate the efficacy of the program in older adults without cognitive impairment. MethodsThis study used a case-control cohort design. The smart speaker-based MMT program comprised 3 training sessions per day, 5 days a week, for 8 weeks. Each training session took approximately 15 minutes. This program was implemented using smart speakers, not human trainers. All participants completed the Mini-Mental State Examination, Subjective Memory Complaints Questionnaire, Verbal Learning Test, Digit Span Test, fluency tests, and a short-form version of the Geriatric Depression Scale before and after training. ResultsA total of 60 subjects (29 in the MMT group and 31 in the control group) participated in the study. The training group showed significant increases in the delayed free recall, digit span forward, digit span backward, and fluency test scores compared with the control group. ConclusionsThis study confirmed the efficacy of smart speaker-based MMT in older adults. Home-based smart speaker-based MMT is not limited with respect to location or constrained by space and may help older adults with subjective cognitive decline without requiring intervention by human professionals.